Efforts to Improve The Professionalism of High School Teachers In Bantul Regency: The Impact of Classroom Action Research On Teaching Performance - Sriyanto; Suyatno; Ishafit (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study discusses the importance of Classroom Action Research (CAR) in improving teacher performance in senior high schools in Bantul Regency, which is a crucial aspect to improve the quality of education in the area. CAR offers a reflection-based approach and collaboration between teachers, allowing them to improve their teaching practices through an active, continuous reflection cycle. The purpose of this study is to explore the impact of CAR on teacher professionalism, focusing on improving their pedagogical skills and managerial abilities in managing heterogeneous classes. This study uses a qualitative method approach, with data triangulation through observation, interviews, and documentation, to obtain a comprehensive picture of the implementation and impact of CAR in senior high schools in Bantul Regency. The study's findings indicate that CAR positively impacts the quality of teaching, collaboration between teachers, and teacher self-reflection, which leads to increased job satisfaction and teacher self-confidence. The novelty found in this study is how CAR can be implemented effectively in the local context of Bantul Regency, with its unique socio-economic challenges and education policies. However, this study has limitations regarding representing other regions and access to teacher training. Recommendations for further research are to examine comparisons between regions and explore the long-term influence of PTK on student academic performance and teacher professionalism.